Applications of additive manufacturing and 3d printing in the manufacture of thermoplastic injection molds - Feriotti, Marco Aurélio; Marcelino, Davi de Medeiros; Pohlmann, Mayara Neves; Martino Neto, José; Rosa, Jorge Luiz (Brazilian Journal of Production Engineering, 2021)
Additive manufacturing (AM) and 3D printing, has been largely applied in different sectors, particularly in the manufacturing of thermoplastic injection molds. Currently, additive manufacturing of metals printing needs a solution that combines high performance with low cost to make this technology more applicable. This research presents a case in a company from the sector where, in many cases, additive manufacturing has already been used in the projects and in the mold manufacturing process. Aiming to support this study, bibliographical analysis were made about the application of additive manufacturing in the tooling of thermoplastic injection molds. Thus, it was possible to observe that there is a trend, in the short and medium term, that the production of molds will suffer an impact, with the coming of this technology, which can mean a change in the conventional methods of mold making, because, in addition to inserts, molds are already being manufactured with use of AM, however, in the application of additive manufacturing it is essential that the process used ensures that the parts are free from defects or porosity. This study also showed that this technology will significantly affect the concepts of new projects, and will result in disruptive changes in conventional methods.